Final Child Rights and Wellbeing Impact Assessment (CRWIA) : extension of coverage of the Freedom of Information (Scotland) Act 2002 (FOISA) to registered social landlords and their subsidiaries.: extension of coverage of the Freedom of Information (Scotland) Act 2002 (FOISA) to registered social landlords and their subsidiaries. (2019) - Unknown
No abstract available